PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. PLAZA MEBEL FURNITURE CENTER PEKANBARU - Rodearni Ginting; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to analyze transformational leadership style and work motivation and its effect on Organizational Citizenship Behavior (OCB) on employees of PT. Plaza Mebel Furniture Center Pekanbaru. Transformational Leadership Style as a variable (X1), Work Motivation as a variable (X2) and Organizational Citizenship Behavior (OCB) as a variable (Y).In this study the population is all permanent employees of PT. Plaza Furniture Furniture Center Pekanbaru, amounting to 72 people. Research data in the form of primary data and secondary data, with questionnaires as research instruments. The results of the analysis used the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test. The results of this study concluded that transformational leadership style and work motivation had an effect on Organizational Citizenship Behavior (OCB) on employees of PT. Plaza Mebel Furniture Center Pekanbaru. With the results of simultaneous verification that F count (5.406)> F table (3.13). So, the hypothesis of transformational leadership style and work motivation simultaneously significantly influence Organizational Citizenship Behavior (OCB) is accepted.  Keywords: Transformational Leadership Style, Work Motivation, Organizational Citizenship Behavior (OCB).